Democratisation and the Labour Struggle: Trade Union Dynamics in Malaysian Borneo and Indonesian Borneo - Syed Annuar, Sharifah Nursyahidah (Journal of Southeast Asian Human Rights, 2024)
Trade unions are proliferating in Malaysia despite the presence of a semi-authoritarian climate. Comparatively, Indonesia is observing a decline in trade unions and respective membership despite a developing democracy. The present study aims to assess the trade unions in Malaysian and Indonesian Borneo that are rarely given attention. The literature revealed that the national culture significantly influences trade unions in both regions. For instance, the trade unions in Malaysian Borneo are highly distinctive compared to those of Peninsular Malaysia. Subsequently, national culture, including individualism and collectivism, uncertainty avoidance, power distance, and masculinity versus femininity, affect the adherence to the national trend. Moreover, internal and external factors, such as union awareness, the commando spirit, cooperative or confrontational attitudes, employment laws, and opinion differences could impact trade unions and democracy. Accordingly, this study conducted case studies on three main economic sectors with high similarities, namely oil and gas, timber, and palm oil in both regions to determine the underlying factors. Although Malaysian and Indonesian Borneo demonstrated significant differences in the observance of national trends, similar democracy challenges, especially marginalisation and disempowerment of workers and trade unions, were observed.